2011
DOI: 10.1103/physreve.84.046402
|View full text |Cite
|
Sign up to set email alerts
|

Gold charge state distributions in highly ionized, low-density beam plasmas

Abstract: We present a systematic study of Au charge state distributions (CSDs) from low density, nonlocal thermodynamic equilibrium plasmas created in the Livermore electron beam ion traps (EBIT-I and EBIT-II). X-ray emission from Ni-like to Kr-like Au ions has been recorded from monoenergetic electron beam plasmas having E beam = 2.66, 2.92, 3.53 and 4.54 keV, and the CSDs of the beam plasmas have been inferred by fitting the collisionally excited line transitions and radiative recombination emission features with syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Progress also arose from the realization that dielectronic recombination must be adequately taken into account. The dominating role of dielectronic recombination in determining the ionization balance of gold ions was recently demonstrated by May et al, who showed that even weak resonances, which merely involved spectator electrons in very high principal quantum numbers with n = 14-17, made a huge difference even in such simple plasmas as those produced by an electron beam in an ion trap [177]. Although the type of dielectronic resonances in this case was highly restricted to a small subset of the multitude of resonances possible in a Maxwellian plasma, there were still too many resonances to perform a full ab initio calculation that included all of the levels with spectators in n = 14-17 for the near-nickellike ionization stages of gold that were formed in the plasma.…”
Section: Accurate Knowledge Of the Ionization Balancementioning
confidence: 98%
See 1 more Smart Citation
“…Progress also arose from the realization that dielectronic recombination must be adequately taken into account. The dominating role of dielectronic recombination in determining the ionization balance of gold ions was recently demonstrated by May et al, who showed that even weak resonances, which merely involved spectator electrons in very high principal quantum numbers with n = 14-17, made a huge difference even in such simple plasmas as those produced by an electron beam in an ion trap [177]. Although the type of dielectronic resonances in this case was highly restricted to a small subset of the multitude of resonances possible in a Maxwellian plasma, there were still too many resonances to perform a full ab initio calculation that included all of the levels with spectators in n = 14-17 for the near-nickellike ionization stages of gold that were formed in the plasma.…”
Section: Accurate Knowledge Of the Ionization Balancementioning
confidence: 98%
“…The measurements were performed on the electron beam ion trap at Livermore. [177]. The sensitivity of the ionization balance calculations to how the atomic processes involving autoionizing levels are treated means that so far no fully adequate calculation exists.…”
Section: Accurate Knowledge Of the Ionization Balancementioning
confidence: 99%
“…Besides this fundamental interest on the relativistic details of electron-electron interaction, investigations of the DR are also mandatory for modeling hot astrophysical and laboratory plasmas, as DR often dominates the recombination rates due to its high resonance strength [19][20][21]. Resonances can thus be used for temperature and density plasma diagnostics [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Electrons in a beam with a nominal energy of 3.6 keV and a 50 eV spread will find lots of resonance to excite. [Figure adaptedfrom[52]. ]…”
mentioning
confidence: 99%